The Relationship of Self-Motivation in Diabetes Mellitus Management with Blood Sugar Levels of Diabetes Mellitus Type II Clients - Berthiana T (Institute of Medico-legal Publications Pvt Ltd, 2020)
The purpose of this study was to determine the relationship of self-motivation to diabetes mellitus (DM) management with blood sugar levels of DM type ii clients in Outpatient Polyclinic Installation in Dr. Doris Sylvanus Hospital Palangka Raya. The research uses descriptive correlational with cross sectional research design. The sampling technique uses purposive sampling. The respondents of this study were 40 people. Data collection using a questionnaire and recording the value of blood sugar from the results of laboratory tests in the client report status. Statistical tests use the Chi-Square test. The results of statistical analysis revealed that self-motivation on clients was in the unfavorable category of 32 people (80%), blood sugar levels were in the high category of 26 people (65%) with a p-value of 0.001 (p <0.05). There is a significant relationship between self-motivation to DM management with blood sugar levels of DM type II clients in the Outpatient Polyclinic Installation of Dr. Doris Sylvanus Hospital Palangka Raya.